2002
DOI: 10.1007/s12043-002-0212-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic behavior of the oxide spinels: Li0.5Fe2.5−2x Al x Cr x O4

Abstract: In order to study the effect of substitution of Fe 3+ by Al 3+ and Cr 3+ in Li 0.5 Fe 2.5 O 4 on its structural and magnetic properties, the spinel system Li 0.5 Al x Cr x Fe 2.5−2x O 4 (x = 0.0, 0.2, 0.4, 0.5, 0.6 and 0.8) has been characterized by X-ray diffraction, high field magnetization, low field ac susceptibility and 57 Fe Mössbauer spectroscopy. Contrary to the earlier reports, about 50% of Al 3+ is found to occupy the tetrahedral sites. The system exhibits canted spin structure and a central paramagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Ferrites are magnetic materials combining insulating and ferrimagnetic properties, and they have long been used in technology [1][2][3][4]. In the classical theory of ferrimagnets [5], Néel had predicted the unusual thermal variation of the spontaneous magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrites are magnetic materials combining insulating and ferrimagnetic properties, and they have long been used in technology [1][2][3][4]. In the classical theory of ferrimagnets [5], Néel had predicted the unusual thermal variation of the spontaneous magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of Cr 3+ ions gives rise to strong B-B interaction [2]. There are reports on the magnetic properties of Al 3+ and Cr 3+ substituted for Fe 3+ in Ni-and Li-ferrites [3][4][5][6] and garnets [7]. The structural study on Al 3+ substituted Cu-ferrites [8] has shown the absence of tetragonal distortion for lower Al content and higher B-site occupancy of Al 3+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the percentage occupation of Fe 3þ ions at the B sites increases from 25% to 40%, while that of Cr 3þ ions at the B sites remains unchanged, thereby strengthening B-B interactions. This induces spin-canting in the octahedral (B) sites, thereby increasing the spin-canting angle with increasing Zn concentration [14,15]. The Nel temperature for each of the Zn x Cu 1Àx Fe 1:2 Cr 0:8 O 4 samples was determined by measuring the temperature at which the hyperfine pattern coalesces into a doublet.…”
Section: Resultsmentioning
confidence: 99%